Autolysis at the disintegrin domain of patagonfibrase, a metalloproteinase from Philodryas patagoniensis (Patagonia Green Racer; Dipsadidae) venom - Peichoto, María Elisa (2010)
Patago-calcium markedly enhanced the azocaseinolytic activity of patagonfibrase. Our findings contribute to the understanding of the structural and mechanistic bases of this family of metalloenzymes that are widely distributed among snake venoms, demonstrating that important post-translational modifications such as proteolysis can also contribute to the diversity and complexity of proteins found in rear-fanged snake venoms.